Face masks as layers of meaning in times of COVID-19. (March 2021) - Tateo, Luca
The pandemic of COVID-19 has brought to the front a particular object: the face mask. I have explored the way people make-meaning of an object generally associated with the medical context that, under exceptional circumstances, can become a presence in everyday life. Understanding how people make meaning of their use is important. Using cultural psychology, I analyse preferences toward different types of face masks people would wear in public. The study involved 2 groups, 44 Norwegian university students and 60 international academics. In particular, I have focused on the role of the mask in regulating people affective experience. The mask evokes safety and fear, it mediates in the auto-dialogue between "I" and "Me" through the "Other", and in the hetero-dialogue between "I" and the "Other" through "Me" The dialogue is characterized by a certain ambivalence, as expected. Meaning-making is indeed the way to deal with the ambivalence of human existence.